The microbiology of beef steaks stored aerobically or anaerobically in vacuum pack films with different oxygen barrier properties. (December 2020) - McSharry, Siobhán; Koolman, Leonard; Whyte, Paul; Bolton, Declan
Highlights: At 2 °C, similar TVC, Enterobacteriaceae and LAB counts were obtained, regardless of packaging film. At 20 °C, medium and high barrier packaged steaks had lower bacterial growth. High barrier packaging (OTR of <3 cm 3 /m 2 ·day· bar) and anaerobic storage maximised shelf-life. Abstract: The objective of this study was to investigate bacterial growth on beef steaks stored under different atmospheric conditions (aerobic, anaerobic and low, medium and high barrier film vacuum packs) at 2 °C and temperature abuse (20 °C) conditions while monitoring changes in physicochemical and colour stability. At 2 °C, packaged steaks did not show significantly (p≥0.05) reduced growth of mesophilic and psychrophilic total viable counts (TVCm and TVCp), Enterobacteriaceae or lactic acid bacteria populations compared to aerobically stored steaks but significantly (p ≤ 0.05) less populations of Pseudomonas and Brochothrix thermosphacta were recorded in high barrier and anaerobic packaging. At 20 °C, medium, high barrier and anaerobic packaged steaks showed significantly (p ≤ 0.05) less growth of TVCm, TVCp, Enterobacteriaceae, Pseudomonas spp. and B. thermosphacta compared to aerobically stored steaks. Overall, high barrier packaging with an oxygen transfer rate (OTR) of <3 cm 3 /m 2 ·day· bar and anaerobic storage both showed the greatest potential at reducing spoilage bacteria on beef ( Pseudomonas and B. thermosphacta ) while retaining the redness of the meat for the longest duration.